Osteoinductive porous biphasic calcium phosphate ceramic as an alternative to autogenous bone grafting in the treatment of mandibular bone critical-size defects - Santos, Paula Sanches; Cestari, Tania Mary; Paulin, Jéssica Botto; Martins, Renato; Rocha, Caroline Andrade; Arantes, Ricardo Vinícius Nunes; Costa, Bruna Carolina [UNESP]; dos Santos, Cássio Morilla [UNESP]; Assis, Gerson Francisco; Taga, Rumio (Wiley, 2018)
The bone-induction capacity of a porous biphasic calcium phosphate (pBCP) using heterotopic implantation in mouse (mHI-model) and its efficacy as substitute for autograft in mandibular critical-size defect in rabbit (rabMCSD-model) was investigated. In mHI-model, pBCP was implanted into the thigh muscles and bone formation was histomorphometrically and immunohistochemically evaluated. In rabMCSD-model, 13 mm bone defects were treated with pBCP or autograft and bone repair comparatively evaluated by radiographic and histomorphometric methods. In mHI-model, formed bone and immunolabeling for bone morphogenetic protein-2 and osteopontin were observed in 90% of pBCP implanted samples after 12 weeks. In rabMCSD-model neither statistically significant difference was found in newly formed bone between pBCP and autograft groups at 4 weeks (18.8 ± 5.5% vs 27.1 ± 5.6%), 8 weeks (22.3 ± 2.7% vs 26.2 ± 5.1), and 12 weeks (19.6 ± 4.7% vs 19.6 ± 2.3%). At 12 weeks, the stability and contour of the mandible were restored in both treatments. Near tooth remaining, pBCP particles were covered by small amount of mineralized tissue exhibiting perpendicular attachments of collagen fiber bundles with histological characteristic of acellular cementum. Within the limitations of this study, it was concluded that pBCP is osteoinductive and able to stimulate the new formation of bone and cementum-like tissues in rabMCSD-model, suggesting that it may be an alternative to treatment of large bone defect and in periodontal regenerative therapy. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 1546–1557, 2018.
Keywords: bone regeneration; bone substitutes; calcium phosphates; heterotopic ossification; mandibular reconstruction